Post-encephalitis Treatment with Encephabol - Sumarmo Sumarmo; Sofjan Ismael; S. M. Lumbantobing; Sri Sudarjati Nasar (Indonesian Pediatric Society, 1974)
The purpose of this investigation is to evaluate the effect of encephabol as seen from the clinical, psychological and electroencephalographical points of view on patients suffering from post-encephalitis and also whether side effects may occur. For comparison and as a control vitamins of the B-complex group which are related to encephabol are given to some patients.